PENGARUH WORK-LIFE BALANCE, KEPUASAN GAJI, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION (Studi Kasus Pada Karyawan Generasi Milenial di Pati) - Rindi Alvia Ningrum; Rauly Sijabat; Fadjar Dharmaputra (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
The purpose of this study is to find out whether work-life balance, salary satisfaction and work environment affect turnover intention in the millennial generation in Pati. The research method used is quantitative research with a descriptive approach conducted on millennial employees in Pati. The total population is all millennial generation employees in Pati. The sampling technique in this study was a non-probability sampling technique. The type used was purposive sampling. The data were obtained from respondents through the Google form. The data collection method was carried out by distributing questionnaires with the Google form according to an interval scale of 1 – 5, and then tabulated using statistical analysis with the SPSS computer program. The results of testing the effect of the work-life balance variable on turnover intention have a positive and significant effect. There is no positive and significant effect of salary satisfaction on tunover intention. The influence of work environment variables on tunrover intention has a positive and significant effect. The effect of the positive work-life balance variable on Turnover Intention is (4.952), while for the negative effect of salary satisfaction the t value is (-1.806). While the effect of positive work environment variables on Turnover Intention is (2.264).